Determinan Tax Avoidance pada Emiten LQ45 dengan Ukuran Perusahaan sebagai Pemoderasi - Santi; Nina Febriana Dosinta; Gita Desyana (Jurnal Literasi Akuntansi, 2025)
Purpose: To test and analyze the determinants of tax avoidance in LQ45 issuers with company size as a moderator. This research in expected to enrich the literature on tax avoidance determinants and provide practical benefits for tax authorities, investors, and related company management. Method: This research adopts a multivariate quantitative approach. During 2018 to 2023 on LQ45 issuers. The purposive sampling technique was used up to 11 companies selected based on the criteria set. The data processing technique begins with data classification and then analyzed using EViews 12 software through multiple regression analysis and moderating regression. Finding: Firm value, profitability, capital intensity simultaneously affect tax avoidance. Partially, firm value has a positive effect on tax avoidance, profitability has a negative effect on tax avoidance, while capital intensity has no positive effect on tax avoidance. Company size as a moderator does not moderate company value, profitability, capital intensity on tax avoidance partially. Novelty: This research presents novelty by integrating firm value, profitability and capital intensity on tax avoidance with firm size as a moderator with agency theory and signal theory approaches in understanding the motivation and implications of tax avoidance in LQ45 listed companies.